Revisión de la evaluación agronómica de especies arbustivas - Maass, Brigitte L.; Schultze-Kraft, Rainer; Argel M., Pedro J. (International Center for Tropical Agriculture, 1996)
Literature on defoliation management of multiple purpose trees and shrubs is reviewed. The most important factors influencing plant performance under defoliation, are the inherent capacity of species to support continuous defoliation, frequency and intensity (height) of cutting, season and age of first cut (more important in slow growing species) when the defoliation is taking place, and plant density. Depending on species and the environment, also interactions among these factors may be significant. Future research needs are discussed